Evidence for a second regulatory binding site on PspF that is occupied by the C-terminal domain of PspA. - Eyleen Sabine Heidrich; Thomas Brüser (PLoS ONE)
PspA is a key component of the bacterial Psp membrane-stress response system. The biochemical and functional characterization of PspA is impeded by its oligomerization and aggregation properties. It was recently possible to solve the coiled coil structure of a completely soluble PspA fragment, PspA(1-144), that associates with the σ54 enhancer binding protein PspF at its W56-loop and thereby down-regulates the Psp response. We now found that the C-terminal part of PspA, PspA(145-222), also interacts with PspF and inhibits its activity in the absence of full-length PspA. Surprisingly, PspA(145-222) effects changed completely in the presence of full-length PspA, as promoter activity was triggered instead of being inhibited under this condition. PspA(145-222) thus interfered with the inhibitory effect of full-length PspA on PspF, most likely by interacting with full-length PspA that remained bound to PspF. In support of this view, a comprehensive bacterial-2-hybrid screen as well as co-purification analyses indicated a self-interaction of PspA(145-222) and an interaction with full-length PspA. This is the first direct demonstration of PspA/PspA and PspA/PspF interactions in vivo that are mediated by the C-terminus of PspA. The data indicate that regulatory binding sites on PspF do not only exist for the N-terminal coiled coil domain but also for the C-terminal domain of PspA. The inhibition of PspF by PspA-(145-222) was reduced upon membrane stress, whereas the inhibition of PspF by PspA(1-144) did not respond to membrane stress. We therefore propose that the C-terminal domain of PspA is crucial for the regulation of PspF in response to Psp system stimuli.